1997
DOI: 10.1002/(sici)1097-0185(199712)249:4<495::aid-ar9>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the smooth-muscle proteins α-smooth-muscle actin and calponin, and of the intermediate filament protein desmin are parameters of cardiomyocyte maturation in the prenatal rat heart

Abstract: The results indicate that alpha-SMA, calponin, and desmin are involved in the myofibrillar development in rat heart. The presence of spatiotemporal differences in the expression of these proteins reveals regional differences in the developmental timing of cardiomyocyte maturation. The maturation process extends from the compact myocardium in the IVS to the left and right ventricular free walls, whereas the atrioventricular junction, the ventricular trabeculae, and developing ventricular conduction system show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 58 publications
(92 reference statements)
5
38
0
Order By: Relevance
“…Compact and trabeculated myocardium are under distinct genetic control, have different myocardial properties, and express different levels of cardiac genes (Sucov et al, 1994;Gassmann et al, 1995;Meyer and Birchmeier, 1995;Franco et al, 1998;Moorman et al, 1998). The finding that the compact ventricular myocardium shows left and right chamber-specific transcriptional properties is consistent with the observation that the LV acquires a compact myocardial morphology before the RV (Ya et al, 1997). The left/right regionalised expression patterns of transgenes, in contrast, tend to extend to both the compact and trabeculated zones of either the left or right ventricle (Kelly et al, 1999).…”
Section: Discussionsupporting
confidence: 65%
“…Compact and trabeculated myocardium are under distinct genetic control, have different myocardial properties, and express different levels of cardiac genes (Sucov et al, 1994;Gassmann et al, 1995;Meyer and Birchmeier, 1995;Franco et al, 1998;Moorman et al, 1998). The finding that the compact ventricular myocardium shows left and right chamber-specific transcriptional properties is consistent with the observation that the LV acquires a compact myocardial morphology before the RV (Ya et al, 1997). The left/right regionalised expression patterns of transgenes, in contrast, tend to extend to both the compact and trabeculated zones of either the left or right ventricle (Kelly et al, 1999).…”
Section: Discussionsupporting
confidence: 65%
“…24,32 The present study also showed that some implanted GFP-positive cells expressed not only SMA, but also desmin and calponin I, which are usually expressed at later stages than SMA during smooth muscle cell development. [33][34][35][36][37][38] Other GFP-positive cells expressed S100 and tubulin beta 3, which are common nerve cell markers, as well as CGRP, which is expressed in afferent nerve cells. Therefore, the implanted GFP-positive cells differentiated into smooth muscle-and nerve-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ES cells can form an organized, functional cardiac conduction system in vitro (White and Claycomb, 2005), a tempting explanation for this arrhythmia induction would be that pace-maker cells are preferentially affected by SMA-FP. An observation favoring this idea is that, during rat heart development, expression of ␣-SMA persists longer in the ventricular conduction system, making it a convenient marker for the ventricular conduction system in the fetal heart (Ya et al, 1997). Nevertheless, given that not all cardiac cells within beating areas in EBs express ␣-SMA, it is possible that hindrance by cell contractility in only the ␣-SMA-positive fraction of cells contributes to the disorganization of the electrical conduction of the signal.…”
Section: Discussionmentioning
confidence: 99%